INVESTIGATION OF EPIDEMIOLOGY AND ETIOLOGY OF LIVER DISEASES AND CHARACTERIZATION OF ITS ASSOCIATION WITH VARIOUS FACTORS - Desai, Namrata A; Kotak, Kishan P; Patel, Snehal S (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: The population of Gujarat is at higher risk of facing non-alcoholic liver diseases therefore it becomes important to examine etiology and epidemiology of liver diseases and to characterize its association to various risk factors. Methods: Patient details such as socioeconomic background, demography, family history, medical history were collected at tertiary care trust hospital in Vadodara district, Gujarat. Causes of disease and various complications associated with the disease were investigated. The reports of various liver function tests were clinically co-related with patient conditions. Results: Out of 137 patients of liver diseases, prevalence of alcoholic patients was 25%. Prevalence of viral infection was found to be 20%. Among all 78% were male and 22% were female and 80% patients were above 40 years of age. Urban population were found to be more susceptible to liver diseases. It was observed that 33% patients were of liver cirrhosis. Diabetes and cardiovascular disorders were most prevalent co-morbidities with 24% and 19.3% respectively. Gamma glutamyl transferase levels were significantly high (p<0.001) in alcoholics while alkaline phosphatase levels were significantly high (p<0.001) in viral manifestations. Hematocrit values also correlate well with the severity of liver diseases. Conclusion: Thus, the present study concludes that gender, age, urbanization, comorbid conditions are risk factors associated with high prevalence of liver disease. Keywords: Alcoholic liver disease, Fatty liver disease, Hepatitis, Liver disease, Non-alcoholic fatty liver disease.